Structure, function and cell dynamics during chaetogenesis of abdominal uncini in Sabellaria alveolata (Sabellariidae, Annelida). Issue 1 (December 2016) - Tilic, Ekin; Bartolomaeus, Thomas
Abstract Background Dynamic apical microvilli of a single cell, called the chaetoblast, inside an ectodermal invagination form the template of annelid chaetae. Changes in the pattern of microvilli are frozen in time by release of chitin, such that the structure of the definitive chaeta reflects its formation. Cellular interactions during chaetogenesis also influence the structure of the chaeta. Analysing chaetogenesis allows for testing hypotheses on the homology of certain chaetal types. We used this approach to test whether the unusual uncini inSabellaria alveolata are homologous to apparently similar uncini in other annelid taxa. Results Our study reveals unexpected details of sabellariid uncini, which mechanically reinforce the neuropodia enabling their use as paddles. The final structure of the chaeta is caused by pulses of microvilli formation and dynamic interaction between the chaetoblast and adjoining follicle cells. Cell dynamics during chaetogenesis of the uncini inSabellaria alveolata exceeds by far that reported in previous studies on the formation of this type of chaetae. Conclusion Despite the superficial similarity of uncini in sabellariids and other annelids, differences in structure and details of formation do not support the homology of this type of chaetae. Chaetogenesis of sabellariid uncini involves unexpected microvilli and cell dynamics, and provides evidence that interactions between cells play a larger role in chaetogenesis than previously expected. In addition to their function as anchors, uncini in Sabellaridae stabilize the paddle-shaped notopodia, as each uncinus possesses a long, thin rod that extends deeply into the notopodium. The rods of all uncini in a single row form a bundle inside the notopodium that additionally serves as a muscle attachment site and thus have a similar function to the inner chaeta (acicula) of errant polychaetes (Aciculata).